Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Interannual variability of net ecosystem productivity in forests is explained by carbon flux phenology in autumn - Chaoyang Wu; Jing M. Chen; T. Andrew Black; David T. Price; Werner A. Kurz; Ankur R. Desai; Alemu Gonsamo; Rachhpal S. Jassal; Christopher M. Gough; Gil Bohrer; Danilo Dragoni; Mathias Herbst; et al. (Global Ecology and Biogeography, 2013)
Aim To investigate the importance of autumn phenology in controlling interannual variability of forest net ecosystem productivity ( NEP ) and to derive new phenological metrics to explain the interannual variability of NEP . Location N orth A merica and E urope. Method Flux data from nine deciduous broadleaf forests ( DBF ) and 13 evergreen needleleaf forests ( ENF ) across N orth A merica and E urope (212 site‐years) were used to explore the relationships between the yearly anomalies of annual NEP and several carbon flux based phenological indicators, including the onset/end of the growing season, onset/end of the carbon uptake period, the spring lag (time interval between the onset of growing season and carbon uptake period) and the autumn lag (time interval between the end of the carbon uptake period and the growing season). Meteorological variables, including global shortwave radiation, air temperature, soil temperature, soil water content and precipitation, were also used to explain the phenological variations. Results We found that interannual variability of NEP can be largely explained by autumn phenology, i.e. the autumn lag. While variation in neither annual gross primary productivity ( GPP ) nor in annual ecosystem respiration ( R e ) alone could explain this variability, the negative relationship between annual NEP and autumn lag was due to a larger R e / GPP ratio in years with a prolonged autumn lag. For DBF sites, a longer autumn lag coincided with a significant decrease in annual GPP but showed no correlation with annual R e . However, annual GPP was insensitive to a longer autumn lag in ENF sites but annual R e increased significantly. Main conclusions These results demonstrate that autumn phenology plays a more direct role than spring phenology in regulating interannual variability of annual NEP . In particular, the importance of respiration may be potentially underestimated in deriving phenological indicators.

Soil respiration is stimulated by elevated CO 2 and reduced by summer drought: three years of measurements in a multifactor ecosystem manipulation experiment in a temperate heathland (CLIMAITE) - Merete B. Selsted; Leon van der Linden; Andreas Ibrom; Anders Michelsen; Klaus S. Larsen; Jane K. Pedersen; Teis N. Mikkelsen; Kim Pilegaard; Claus Beier; Per Ambus (Global Change Biology, 2012)
This study investigated the impact of predicted future climatic and atmospheric conditions on soil respiration ( R S ) in a Danish Calluna‐Deschampsia‐ heathland. A fully factorial in situ experiment with treatments of elevated atmospheric CO 2 (+130 ppm), raised soil temperature (+0.4 °C) and extended summer drought (5–8% precipitation exclusion) was established in 2005. The average R S , observed in the control over 3 years of measurements (1.7 μmol CO 2 m −2 sec −1 ), increased 38% under elevated CO 2 , irrespective of combination with the drought or temperature treatments. In contrast, extended summer drought decreased R S by 14%, while elevated soil temperature did not affect R S overall. A significant interaction between elevated temperature and drought resulted in further reduction of R S when these treatments were combined. A detailed analysis of short‐term R S dynamics associated with drought periods showed that R S was reduced by ~50% and was strongly correlated with soil moisture during these events. Recovery of R S to pre‐drought levels occurred within 2 weeks of rewetting; however, unexpected drought effects were observed several months after summer drought treatment in 2 of the 3 years, possibly due to reduced plant growth or changes in soil water holding capacity. An empirical model that predicts R S from soil temperature, soil moisture and plant biomass was developed and accounted for 55% of the observed variability in R S . The model predicted annual sums of R S in 2006 and 2007, in the control, were 672 and 719 g C m −2 y −1 , respectively. For the full treatment combination, i.e. the future climate scenario, the model predicted that soil respiratory C losses would increase by ~21% (140–150 g C m −2 y −1 ). Therefore, in the future climate, stimulation of C storage in plant biomass and litter must be in excess of 21% for this ecosystem to not suffer a reduction in net ecosystem exchange.

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Linking flux network measurements to continental scale simulations: ecosystem carbon dioxide exchange capacity under non‐water‐stressed conditions - KATHERINE E. OWEN; JOHN TENHUNEN; MARKUS REICHSTEIN; QUAN WANG; EVA FALGE; RALF GEYER; XIANGMING XIAO; PAUL STOY; CHRISTOF AMMANN; ALTAF ARAIN; MARC AUBINET; MIKA AURELA; et al. (Global Change Biology, 2007)
This paper examines long‐term eddy covariance data from 18 European and 17 North American and Asian forest, wetland, tundra, grassland, and cropland sites under non‐water‐stressed conditions with an empirical rectangular hyperbolic light response model and a single layer two light‐class carboxylase‐based model. Relationships according to ecosystem functional type are demonstrated between empirical and physiological parameters, suggesting linkages between easily estimated parameters and those with greater potential for process interpretation. Relatively sparse documentation of leaf area index dynamics at flux tower sites is found to be a major difficulty in model inversion and flux interpretation. Therefore, a simplification of the physiological model is carried out for a subset of European network sites with extensive ancillary data. The results from these selected sites are used to derive a new parameter and means for comparing empirical and physiologically based methods across all sites, regardless of ancillary data. The results from the European analysis are then compared with results from the other Northern Hemisphere sites and similar relationships for the simplified process‐based parameter were found to hold for European, North American, and Asian temperate and boreal climate zones. This parameter is useful for bridging between flux network observations and continental scale spatial simulations of vegetation/atmosphere carbon dioxide exchange.

Linking flux network measurements to continental scale simulations: ecosystem carbon dioxide exchange capacity under non-water-stressed conditions - KATHERINE E. OWEN; JOHN TENHUNEN; MARKUS REICHSTEIN; QUAN WANG; EVA FALGE; RALF GEYER; XIANGMING XIAO; PAUL STOY; CHRISTOF AMMANN; ALTAF ARAIN; MARC AUBINET; MIKA AURELA; et al. (Global Change Biology, 2007)

Pan‐European δ 13 C values of air and organic matter from forest ecosystems - Deborah Hemming; Dan Yakir; Per Ambus; Mika Aurela; Cathy Besson; Kevin Black; Nina Buchmann; Regis Burlett; Alessandro Cescatti; Robert Clement; Patrick Gross; André Granier; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ 13 C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ 13 C values derived from large‐scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem‐scale δ 13 C values. In this framework, we also tested the potential of δ 13 C in canopy air and plant organic matter to record regional‐scale ecophysiological patterns. Our network estimates for the mean δ 13 C of ecosystem respired CO 2 and the related ‘discrimination’ of ecosystem respiration, δ er and Δ er , respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ 13 C values derived from regional‐scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional‐scale atmospheric sampling programs generally capture ecosystem δ 13 C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δ er . From west to east, across the network, there was a general enrichment in 13 C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13 C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δ er values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature ( T a ), but not significantly with monthly average precipitation ( P m ). In contrast, in 2002 (a much wetter peak season), δ er was significantly related with T a , but not significantly with VPD and RH. The important role of plant physiological processes on δ er in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time‐lag analyses of δ er vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δ er and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δ er signal during this season. Organic matter δ 13 C results showed progressive 13 C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13 C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ 13 C values of organic matter of any of the plant components did not well represent short‐term δ er values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.

Large seasonal changes in Q 10 of soil respiration in a beech forest - IVAN A. JANSSENS; KIM PILEGAARD (Global Change Biology, 2003)
We analyzed one year of continuous soil respiration measurements to assess variations in the temperature sensitivity of soil respiration at a Danish beech forest. A single temperature function derived from all measurements across the year ( Q 10 = 4.2) was adequate for estimating the total annual soil respiration and its seasonal evolution. However, Q 10 's derived from weekly datasets ranged between three in summer (at a mean soil temperature of 14 °C) and 23 in winter (at 2 °C), indicating that the annual temperature function underestimated the synoptic variations in soil respiration during winter. These results highlight that empirical models should be parameterized at a time resolution similar to that required by the output of the model. If the objective of the model is to simulate the total annual soil respiration rate, annual parameterization suffices. If however, soil respiration needs to be simulated over time periods from days to weeks, as is the case when soil respiration is compared to total ecosystem respiration during synoptic weather patterns, more short‐term parameterization is required. Despite the higher wintertime Q 10 's, the absolute response of soil respiration to temperature was smaller in winter than in summer. This is mainly because in absolute numbers, the temperature sensitivity of soil respiration depends not only on Q 10 , but also on the rate of soil respiration, which is highly reduced in winter. Nonetheless, the Q 10 of soil respiration in winter was larger than can be explained by the decreasing respiration rate only. Because the seasonal changes in Q 10 were negatively correlated with temperature and positively correlated with soil moisture, they could also be related to changing temperature and/or soil moisture conditions.